Deep Learning Pedagogy dalam Perspektif Konstruktivisme: Systematic Literature Review terhadap Pemahaman Konseptual - Ngganiyatur Rochmah; Alifiani Alifiani (FKIP Universitas Mataram, 2026)
The development of modern education requires a paradigm shift in learning from mere knowledge transfer to a meaningful learning process oriented towards conceptual understanding. However, classroom learning practices are still dominated by surface learning that emphasizes memorization rather than deep conceptual understanding. This condition highlights the importance of applying pedagogical approaches that can foster active student involvement in knowledge construction, such as deep learning pedagogy rooted in constructivism principles. This study aims to systematically review various studies examining the relationship between deep learning pedagogy, constructivism, and students' conceptual understanding. The study was conducted using the Systematic Literature Review (SLR) method with PRISMA guidelines for articles published in 2021–2025, resulting in 15 relevant articles for thematic analysis. The results show that the integration of deep learning pedagogy and constructivism effectively improves conceptual understanding through project-based, problem-based, and reflective learning. The conclusion of the study confirms that the synergy of these two approaches strengthens the interconnection between concepts, develops critical thinking, and shapes independent and reflective learners in line with the demands of modern education.